Nigeria - Policy Options for Growth and Stability : Volume 1. Main Report - World Bank (Washington, DC, 2013)
This report represents an effort to identify policy options for long-run growth and poverty reduction that are compatible with the high degree of macroeconomic volatility and challenging institutional realities faced by Nigerian policy makers. The report includes the following key messages: a) The Nigerian economy is not merely volatile; it is one of the most volatile economies in the world. b) There is evidence that this volatility has adversely affected not only Nigeria's historical growth record but also the performance of World Bank projects in Nigeria. c) Sustained future growth and poverty reduction are unlikely without a significant reduction in volatility. c) Oil price fluctuations drive only part of Nigeria's volatility, policy choices have also contributed to the problem. d) Policy choices are available that can help accelerate growth and thus help reduce the percentage of people living in poverty. To conclude, the report identifies several policy options that may help Nigerian make the transition to a high growth, low poverty economy despite the current challenges. More work will be required to further test and deepen the ideas put forth here, but the effort will bring its own rewards.